THIAMINE IMPACT ON THE RATES OF H2O2 DECOMPOSITION IN AQUEOUS SOLUTION AND CUMENE INITIATED AUTOOXIDATION IN EMULSIONS (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
It is shown that in alkaline medium thiamine (TA) results in H2O2 decomposition rate decrease, but in acidic medium inhibits H2O2 decomposition catalyzed by Fe(II) cations, which occurs mainly by radical-chain mechanism. In our early works it was established that in alkaline medium approximately 16% of H2O2 is being decayed with radical formation. So, TA mainly acts in alkaline medium on the rate of H2O2 decomposition, which occurs by radical mechanism. TA·HCl also inhibits the cumene initiated autooxidation, which occurs by radical-chain mechanism with degenerated branching. During autooxidation R• and ROO• free radicals are formed. It is assumed that TA, as well TA·HCl effectively react with free radicals R• and ROO•.
Keywords: thiamine; radical-chain mechanism; cumine autooxidation; rate of H$_2$O$_2$ decomposition